Refinement and Evaluation of the Critical Thinking Self-Assessment Scale. - Barry Hultquist, Teresa; Kupzyk, Kevin; LaFramboise, Louise; Leeseberg Stamler, Lynnette (Journal of Nursing Measurement, 2025)
Background and Purpose: Critical thinking (CT) skills are necessary tools for enhancing patient care. The Critical Thinking Self-Assessment Scale (CTSAS) was based on Facione et al.'s (1990) schema of 6 CT skills and 16 subskills. Although early results indicated a strong instrument, it was lengthy at 115 items. The purpose of the study was to statistically reduce the number of items in the instrument. Methods: Using a sample of 712 undergraduate nursing students, item analysis and confirmatory factor analysis were used to determine items to retain and delete. The scale was validated by comparing to the Need for Cognition Scale. Results: Items were reduced to 46 and spread over the 16 subskills. Conclusions: The revised CTSAS is a valid, reliable tool that has been greatly reduced in length without compromising its psychometric properties. Faculty could use the measure as a reflection of students' levels on these skills and design learning activities to target problem areas.